PENERAPAN MODEL COOPERATIVE LEARNING METODE THINK PARE SHARE SEBAGAI UPAYA PENINGKATAN PRESTASI MATA KULIAH EKONOMI MONETER - Ninik Srijani (Universitas PGRI Madiun, 2013)
This study aims to improve the academic achievement of monetary Economics course through Cooperative Learning Model Type TPS ( Think - Pair - Share) on Economic Education students. The subjects in this study were students who take courses Monetary Economics Odd Semester 2012/2013. Number of students 31 data coUection by observation techniques and evaluation of learning outcomes, and then ana Iyzed with a formula to determine the percentage increase in each cycle, while dle action research procedures through 2 cycles and each cycle consisted of 4 series of activities carried out are 1 ) Planning; 2 ) Implementation; 3 ) Observation, and 4) Reflection. Method of data collection is done by using the observation and evaluation of learning. Observations are used to determine the activity of students in the learning process by using a model of Cooperative Type TPS (Think - Pair - Share ). while the evaluation is used to determine the achievement of monetary economics courses The results of the observation and evalu- ation of student learning outcomes Prodi Economic Education bas increased. This is indicated by the observation of the lndidvidu active students in the learning process bas increased, where the interest and attention of students to the material presented first cycle of the original 61.29% to 83.87%, tbe activity asks students in the first cycle of the original 54, 84% to 71 %, active students and issue an opinion in response to the first cycle of the original 48.39% to 62.29%, level of student discipline in the process of learning to learn in the first cycle the original 64.52% to 80.64%. Being in a group activ- ity of students in the learning process has increased, where the interest and attention of students to the first cycle of the material presented is original 51.61% to 74.19%, the activity asks students in the first cycle of the original 48.39% to 64,52%, active students and issue an opinion in response to the first cycle of the original 48.39% to 74.19%, level of student discipline in the process of learning to learn in the first cycle the original 64.74% to 83.87%. For evaluation of learning in the first cycle masiswa the above aver-age learning initially increased to 64.74% 83.87% students below average dropped to 32.26% 16.31. Based on the research results of the second cycle, it can be concluded that the model learning SMT Type Cooperative ( Think - Pair - Share) can improve the learning achievement of Monetary Economics courses.